Structure of the petioles and costae of Mexican and Central American species of Pteris (Polypodiopsida, Pteridaceae) - Palacios-Rios, Mónica; Gabriel Y Galán, Jose María; Prada, Carmen; Rico-Gray, Victor (Phytotaxa, 2019)
Given the taxonomic complexity of the genus Pteris in the Neotropics, the present work aims to collect information about the anatomy of the petioles and the costae of native, adventitious, and introduced Mexican and Central American species of Pteris, and to analyse its taxonomic potential. We collected fresh and dried samples from 26 species, making histological sections by hand. With the naked eye or with a dissection microscope, the colour and size of the axes, and the characters of the awns were recorded. Other characters (indument, anatomy, specifically the stele) were observed in a compound microscope. The type of stele of the petiole, characterized by the shape of xylem, appeared to be an important taxonomic character because it presents a remarkable correlation with some of the groups formed by spore type. Some of these groups of Mesoamerican species of Pteris, formed by means of morphological criteria (petiole xylem + spore) fit very well certain clades established by means of molecular characters.